Stereolithographic Additive Manufacturing of Zirconia Electrodes with Dendritic Patterns for Aluminum Smelting - Masaya Takahashi (Applied Sciences, 2021)
Zirconia electrodes with dendritic patterns were fabricated by stereolithographic additive manufacturing (STL-AM). A solid electrolyte of yttria-stabilized zirconia (YSZ) was selected for oxygen separation in the molten salt electrolysis of aluminum smelting without carbon dioxide excretion. Thereafter, 4, 6, 8 and 12-coordinated dendritic structures composed of cylindrical lattices were designed as computer graphics. The specific surface area of each structure was maximized by changing the aspect ratio. The spatial profile and surface pressure of the hot liquid propagation in the dendrite patterns were systematically visualized by computational fluid dynamics (CFD). During the fabrication process, a photosensitive resin containing zirconia particles was spread on a substrate, and an ultraviolet (UV) laser beam was scanned to create a two-dimensional (2D) cross-section. Through layer laminations, three-dimensional (3D) objects with dendritic structures were successfully fabricated. The ceramics were obtained through dewaxing and sintering.